2016
DOI: 10.1002/tox.22369
|View full text |Cite
|
Sign up to set email alerts
|

Particulate emissions from the combustion of birch, beech, and spruce logs cause different cytotoxic responses in A549 cells

Abstract: According to the World Health Organization particulate emissions from the combustion of solid fuels caused more than 110,000 premature deaths worldwide in 2010. Log wood combustion is the most prevalent form of residential biomass heating in developed countries, but it is unknown how the type of wood logs used in furnaces influences the chemical composition of the particulate emissions and their toxicological potential. We burned logs of birch, beech and spruce, which are used commonly as firewood in Central a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 36 publications
(46 reference statements)
3
37
3
2
Order By: Relevance
“…In addition, Al and ƩPAHs in PM 0.4–1 from biomass fuel combustion showed a positive correlation with DNA damage; (see Table 4). These results are in agreement with the studies of Kasurinen et al (Kasurinen et al, 2016, 2015b) who reported a correlation between Al and Ca contents of wood smoke particles and observed toxic effects. Genotoxicity of PAHs contained in PM from biomass fuel combustion was also observed in other studies (Danielsen et al, 2009; Tapanainen et al, 2011).…”
Section: Resultssupporting
confidence: 94%
“…In addition, Al and ƩPAHs in PM 0.4–1 from biomass fuel combustion showed a positive correlation with DNA damage; (see Table 4). These results are in agreement with the studies of Kasurinen et al (Kasurinen et al, 2016, 2015b) who reported a correlation between Al and Ca contents of wood smoke particles and observed toxic effects. Genotoxicity of PAHs contained in PM from biomass fuel combustion was also observed in other studies (Danielsen et al, 2009; Tapanainen et al, 2011).…”
Section: Resultssupporting
confidence: 94%
“…At the cellular level, several in vitro studies have shown the proinflammatory effects of biomass smoke exposure. Contact to wood and coal combustion from PM induced an increased production of chemokines, like monocyte chemoattractant protein (MCP)-1 and IL-8 in the NSCLC A549 cell line [10,11], while other combustion particles induced differential pro-inflammatory responses [10,[12][13][14][15]. Mechanistically, wood smoke induces the production of reactive oxygen species (ROS) impacting on the oxidative/reductive state of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Besides easy storage and transport, pellets are currently found to be an efficient and relatively clean fuel for residential heating. Several studies found significantly lower emissions of PM and hazardous organic substances for small-scale pellet combustion compared to log wood combustion [15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…已有研究使用的呼吸暖体假人处于站 立或坐姿状态时, 嘴巴呼出气体的方向是水平的 [6,46,74] , 但是鼻子呼出气流的方向比较复杂, 通常沿水平方向 向下倾斜45°, 并且与垂直方向保持30°的分离角 [6,49] , 符合Gupta等人 [46] [76] , 这些飞沫携带数百万个细菌, 是引起呼吸道传染病的主要原因 [77] . 除动物模型之外, Dilger等人 [90] 、Kasurinen等人 [91] 和Marchetti等人 [92] 使用体外细胞培养法, 通过对人体 [93] . 由于当前体外细胞培养模型的局限 性, Huh等人 [94] 基于微流控技术的细胞装置, 建立体外 肺芯片, 将多个器官组织信息集成在一个单独的芯片 上, 形成"器官-芯片"系统 [95] , 更好地模拟和控制生理 微环境, 可以较快地观察到肺部疾病患者在相关暴露 环境下引起的分子、细胞和组织水平的特异性反应, 对靶向治疗和生物标记物研究具有重要意义 [96] .…”
Section: 研究边界层流场特性 影响人体周围边界层的因素较 多 主要包括房间温度、姿势、服装热阻unclassified